Using the HELIOS facility for assessment of bundle-jacket thermal coupling in a CICC. (December 2016) - Lacroix, B.; Rousset, B.; Cloez, H.; Decool, P.; Duchateau, J.L.; Hoa, C.; Luchier, N.; Nicollet, S.; Topin, F.
Highlights: An experiment was performed for assessing bundle-jacket thermal coupling in a CICC. The mock-up was made of an ITER TF conductor equipped with Cu sleeves and heaters. Bundle-jacket Heat Transfer Coefficient was found in the range 300–500 W m −2  K −1 . Complementary experiments would be useful for investigating HTC inside bundle. Abstract: In a Cable In Conduit Conductor (CICC) cooled by forced circulation of supercritical helium, the heat exchange in the bundle region can play a significant role for conductor safe operation, while remaining a quite uncertain parameter. Heat exchange between bundle and jacket depends on the relative contributions of convective heat transfer due to the helium flow inside the bundle and of thermal resistance due to the wrappings between the cable and the conduit. In order to qualify this thermal coupling at realistic operating conditions, a dedicated experiment on a 1.2 m sample of ITER Toroidal Field (TF) dummy conductor was designed and performed in the HELIOS test facility at CEA Grenoble. Several methods were envisaged, and the choice was made to assess bundle-jacket heat transfer coefficient by measuring the temperature of a solid copper cylinder inserted over the conductor jacket and submitted to heat deposition on its outer surface. The mock-up was manufactured and tested in spring 2015. Bundle-jacket heat transfer coefficient was found in the range 300–500 W m −2  K −1 . Results analysis suggests that the order of magnitude of convective heat transfer coefficient inside bundle is closer to Colburn–Reynolds analogy than to Dittus–Boelter correlation, and that bundle-jacket thermal coupling is mainly limited by thermal resistance due to wrappings. A model based on an equivalent layer of stagnant helium between wraps and jacket was proposed and showed a good consistency with the experiment, with relevant values for the helium layer thickness.